Scale Up Usaha Industri Rumah Tangga Kue Lumpur di Kelurahan Kedungkandang Kota Malang - Afifuddin Afifuddin; Abdul Rani; Muhammad Agus Salim; Margianto Margianto; Nisa’us Sholikah; Rini Rahayu Kurniati; Ika Nuriyanti; Ita Suhermin Ingsih; Anies Fuady (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The problems faced by the IRT 'Siti Rochaniyah' household scale business is the lack of production equipment in the form of oil filters and product processing methods that do not pay attention to sanitation and hygiene and there is no bookkeeping of business finances. Implementing this service program aims to increase the productivity and income of 'Siti Rochaniyah' Home Industry (IRT) partners through increasing producers' knowledge and skills in production and financial management. The method for implementing this program is through counseling, training and assistance to the owners and employees of IRT 'Siti Rochaniyah'. The results of implementing the service program include: availability of a mud cake oven to increase production; increasing partners' knowledge about sanitation and hygiene principles; and Increasing partners' understanding and skills for financial bookkeeping with business management with the POAC (Planning Organizing Actuating Controlling) concept.